2022
DOI: 10.1186/s13089-022-00279-1
|View full text |Cite
|
Sign up to set email alerts
|

International consensus conference recommendations on ultrasound education for undergraduate medical students

Abstract: Objectives The purpose of this study is to provide expert consensus recommendations to establish a global ultrasound curriculum for undergraduate medical students. Methods 64 multi-disciplinary ultrasound experts from 16 countries, 50 multi-disciplinary ultrasound consultants, and 21 medical students and residents contributed to these recommendations. A modified Delphi consensus method was used that included a systematic literature search, evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 161 publications
0
46
0
2
Order By: Relevance
“…The goal of SCPEC was to generate consensus around a list of recommendations from a group of student leaders and physicians on POCUS education in Canadian UGME. This initiative is uniquely different from other POCUS education consensus efforts as it was primarily driven by medical student stakeholders, rather than faculty experts 14 , 15 . For example, in Hoppman et al’s international consensus initiative, students were only implicated in the early stages of consensus iteration and had their work modified by consultants.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of SCPEC was to generate consensus around a list of recommendations from a group of student leaders and physicians on POCUS education in Canadian UGME. This initiative is uniquely different from other POCUS education consensus efforts as it was primarily driven by medical student stakeholders, rather than faculty experts 14 , 15 . For example, in Hoppman et al’s international consensus initiative, students were only implicated in the early stages of consensus iteration and had their work modified by consultants.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that ultrasound-guided cannulation can easily be implemented in clinical routine [ 9 ]. This may also be due to an increasingly integration of ultrasound education during medical school in nearly all medical disciplines [ 10 12 ], which enables young physicians to learn ultrasound-guided techniques more easily.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Simulation education for vascular access is expected to continue to grow in educational content and method. [ 26 ] Self-learning through a web-based learning system is one of the leading candidates.…”
Section: Discussionmentioning
confidence: 99%